Beautiful Day e Sunday Bloody Sunday: uma análise semiótica de letras de canções populares - Succi, Simone Cristina (2011)
This resource has, in constituted corpus, two contemporaneous popular songs written and sung in English by the Irish band U2, which will be analyzed based on the French semiotics theory-methodological referential. The songs, called Beautiful Day and Sunday Bloody Sunday, are analyzed from their internal structure aiming its poetical and multi significant character. With these points, elements of sense generative path, related to the semiotics of the action, are applied to them, specifically focusing its narrative and discursive levels. Thus, it is searched to observe the texts linguistic-discursive organization, specially centered on the semantics of the speech, which is, on the description of the figurative and thematic ways of the texts as well as on the discursive syntax, describing the projections of space, time and of the actors. Thus, using the enunciator unveiling strategies, it is expected to learn the dialogical relationship manifested on the texts and the voices heard on them focusing on the texts discursive levels. Otherwise, the examination of some semi-symbolic relationships and the reflection about the concept of aesthesia has made it possible to unveil its poetical character, which was tried to be associated to the songs.